OPERATIVE CORRECTION OF ARRIVAL AND DEPARTURE FLOW OF AEIRCRAFT AT THE AERODROME - G. N. Lebedev; V. B. Malygin (Научный вестник МГТУ ГА, 2016)
The problem of optimal correction of the scheduled time of take-off and landing aircraft using a single runway (RW), in conditions of high air traffic intensity at which the probability of a conflict between the takeoff and landing reaches a critical value.The efficient approach that allows to solve the problem of safety effectively using the method of "penalty" functions given the additional loss of fuel in case of delays of departure and arrival is proposed.The advantages of the suboptimal solution compared to accept today as a "team" solution to the conflict of the departure and arrival aerodrome is shown.